APEC as an Institution. Multilateral governance in the Asia-Pacific - FEINBERG, Richard E (Institute Southeast Asian Studies, 2003)
APEC is an experimental multilateralism, relying not on a large bureaucracy but rather upon national governmental agencies, semi-autonomous inter-governmental committees and "virtual" associations. Organized around the principles of consensus, voluntarism and unilateralism, APEC has eschewed binding agreements enforced through monitoring and robust compliance mechanisms. This volume assesses the strengths and weaknesses of APEC's "soft" institutionalism, and its capstone policy report, "Remaking APEC", identifies reforms that would close the credibility gap between APEC's promises and accomplishments. Chapters by leading scholars at APEC study centres investigate APEC's core agenda - trade and investment liberalization and capacity building - delve into the inner workings of APEC's bureaucracy, and explore APEC's interactions with civil society, including the private sector and NGOs. This volume contains both the policy report and in-depth specialized studies.